2020
DOI: 10.3390/antiox9111140
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Methane Generation during Methanogenesis by Chemically Modified Humic Compounds

Abstract: The introduction of various concentrations of chemically modified humic compounds (HC) with different redox characteristics into the media with free and immobilized anaerobic consortia accumulating landfill gases was studied as approach to their functioning management. For this purpose, quinone (hydroquinone, naphthoquinone or methylhydroquinone) derivatives of HC were synthesized, which made it possible to vary the redox and antioxidant properties of HC as terminal electron acceptors in methanogenic systems. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…It could be concluded that the directed modification of HS with phenolic centers is a promising tool for preparing humic antioxidants with the desired properties (Figure 8). We have recently demonstrated good prospects of this approach for suppressing methane emission by consortium of methanogenic bacteria [46]: addition of 2-OH-naphthoquinone-HA-derivative into cultivation medium substantially reduced the rate and the amount of the emitted methane, while addition of fulvic acids and their hydroquinone derivatives stimulated the production of methane. From an agricultural perspective, it might be suggested that fulvic acids, in particular, those modified with hydroquinones, could possess enhanced electron-shuttling capacity, which is related to ability of humic substances for eliciting biostimulating activity on plant growth [47].…”
Section: Discussionmentioning
confidence: 99%
“…It could be concluded that the directed modification of HS with phenolic centers is a promising tool for preparing humic antioxidants with the desired properties (Figure 8). We have recently demonstrated good prospects of this approach for suppressing methane emission by consortium of methanogenic bacteria [46]: addition of 2-OH-naphthoquinone-HA-derivative into cultivation medium substantially reduced the rate and the amount of the emitted methane, while addition of fulvic acids and their hydroquinone derivatives stimulated the production of methane. From an agricultural perspective, it might be suggested that fulvic acids, in particular, those modified with hydroquinones, could possess enhanced electron-shuttling capacity, which is related to ability of humic substances for eliciting biostimulating activity on plant growth [47].…”
Section: Discussionmentioning
confidence: 99%
“…This LCA publication was cited with respect to the site selection for landfills [153,154] and in a study which yielded the controversial statement that "recycling metals except gold had more negative environmental impacts than mining" [155]. Further citing studies deal with environmental impacts of combustion-based energy production [156], composting on closed landfill sites [157], bioreactor landfills [158], suppression of methane generation [159], modelling of landfill gas production [160], organic waste enrichment [161]. Within NEW-MINE, LCA was also applied to compare smelting of MSWI bottom ash with the state-of-the-art mineral process-ing approach and revealed that the energy demand for smelting processes overrules, with respect to global warming, the positive effect of secondary raw material production [162].…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…The addition of HC derivatives enriched with quinonones at concentrations above 1 g/l notably reduced the energy status of cells and the efficiency of methanogenesis catalyzed by various anaerobic consortia [3].…”
mentioning
confidence: 99%